Rancang Bangun Marketplace Umkm Produk Kerajinan Tangan Di Kabupaten Malinau Kalimantan Utar - Bestario, Bestario; Agustina, Rini; Susanto, Gaguk (Department of System Information, 2025)
Malinau Kota District is a sub-district in Malinau Regency, North Kalimantan Province, Indonesia. This sub-district serves as middle of directorate and commercial activity in Malinau Regency. The economy in Malinau Kota District is supported by the trade, agriculture, and handicraft sectors. This region is renowned for its local craft potential, reflecting the richness of the region's culture. Furthermore, Malinau Kota offers strategic access as a gateway to the hinterland, making it a hub for local economic development, including the UMKM sector. The design and construction of a UMKM Marketplace for Handicraft Products in Malinau Regency, North Kalimantan, aims to utilize e-commerce technology as a means of promoting UMKM products nationally and internationally. This portal is designed to increase the visibility of local handicraft products, thereby expanding market share and introducing the potential of the Malinau region to the wider community. The research suggests that strengthen the competitiveness of Malinau's handicraft products in the global market.